Suction caisson foundations for offshore wind energy: cyclic response in sand and sand over clay. Issue 10 (22nd November 2018) - Zhu, Fang Yuan; Bienen, Britta; O'Loughlin, Conleth; Cassidy, Mark Jason; Morgan, Neil
Abstract : This technical note considers experimental data on the long-term response of a suction caisson in sand and sand over clay to lateral cyclic loading. Installation of the caisson under suction in a geotechnical centrifuge provides insight into the contribution of this installation process, as well as the effects that soil drainage and consolidation in the clay layer have on the accumulated caisson rotation and change in stiffness. The tests focused on sand over clay, and considered variations in the cyclic load magnitude and symmetry. One-way cyclic loading in sand over clay is seen to result in higher rotation than two-way loading, which contrasts with findings from previous studies in sand. Excess pore pressure dissipation in the clay layer leads to strength increases that stabilise caisson rotation and increase stiffness. The rate of accumulation in caisson rotation is observed to be the same from centrifuge and single gravity tests, while the initial rotation differs with stress level, drainage regime, loading magnitude, soil profile and installation method. The centrifuge tests are considered collectively with equivalent single gravity tests to form a basis for predicting the long-term response of a monopod suction caisson.